Sulfur and nitrogen interaction affects onion yield and post-harvest quality - Cipriano, Patriciani Estela; José Armani Borghi, Edinei; Santana Chales, Amanda; Barra Netto-Ferreira, Julia; Trevizam, Anderson Ricardo; Silva, Maria Ligia de Souza; Guilherme, Luiz Roberto Guimarães (Journal of plant nutrition, 2024)
Ionic interactions affect the mineral composition of plants, which can cause nutritional disorders with reflections on yield, post-harvest quality, and food safety. Thus, this study evaluated the interaction between nitrogen (N) and sulfur (S) and its effects on onion production and post-harvest quality. The study was conducted in a completely randomized design, with a 3 × 5 factorial scheme and four replications. The treatments consisted of a combination of three S rates (0, 20, and 40 mg dm −3 ) and five N rates (0, 40, 60, 80, and 100 mg dm −3 ), applied in the form of calcium sulfate (CaSO 4· 2H 2 O) and urea, respectively. It was observed that the interaction between N and S negatively affected onion production, reducing the gain of both fresh and dry mass of the bulb. The N/S ratio ranged from 16.5 to 26.2 and was not influenced by the interaction between N and S. Onion pungency was classified as intermediate. The higher pungency value was obtained with the application of 100 mg dm −3 of N, and 40 mg dm −3 of S. The application of N when combined with 20 mg dm −3 of S contributed to increasing titratable acidity and soluble solids content of onion cv. Diamantina.